1993
DOI: 10.1002/pro.5560021210
|View full text |Cite
|
Sign up to set email alerts
|

MIF proteins are theta‐class glutathione S‐transferase homologs

Abstract: MIF proteins are mammalian polypeptides of approximately 13,000 molecular weight. This class includes human macrophage migration inhibitory factor (MIF), a rat liver protein that has glutathione S-transferase (GST) activity (TRANSMIF), and the mouse delayed early response gene 6 (DER6) protein. MIF proteins were previously linked to GSTs by demonstrating transferase activity and observing N-terminal sequence homology with a mu-class GST (Blocki, EA., Schlievert, P.M., & Wackett, L.P., 1992, Nature360, 269-270)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…This showed that: (i) MIF shares 25-35% sequence identity within the first 30 amino acids of GSTs; (ii) a hydroxyl-containing active site residue of GSTs (serine for 0-class GST and tyrosine for a-, ir-, and ,u-class GSTs) is replaced by a threonine at the equivalent position of MIF; and (iii) polyclonal antibodies raised to a liver MIF preparation cross-react with 0-class GST (9,34). Nevertheless, the hypothesis that MIF is related to GST is controversial and has been challenged by the lack of significant sequence homology along the entire polypeptide of MIF, the large difference in size between MIF (13 kDa) and GST (26 kDa) (35), and the absence of GST activity in purified and otherwise biologically active recombinant MIF (21,36).…”
Section: Resultsmentioning
confidence: 99%
“…This showed that: (i) MIF shares 25-35% sequence identity within the first 30 amino acids of GSTs; (ii) a hydroxyl-containing active site residue of GSTs (serine for 0-class GST and tyrosine for a-, ir-, and ,u-class GSTs) is replaced by a threonine at the equivalent position of MIF; and (iii) polyclonal antibodies raised to a liver MIF preparation cross-react with 0-class GST (9,34). Nevertheless, the hypothesis that MIF is related to GST is controversial and has been challenged by the lack of significant sequence homology along the entire polypeptide of MIF, the large difference in size between MIF (13 kDa) and GST (26 kDa) (35), and the absence of GST activity in purified and otherwise biologically active recombinant MIF (21,36).…”
Section: Resultsmentioning
confidence: 99%
“…Since MIF has been shown to have DDCT activity, it is likely that DDCT may have a similar physiological role to that of MIF [41]. Interestingly, MIF was previously suggested to show sequence similarities to Mu-and Theta-class GSTs, and was reported to have GST activity [42,43]. Although an evolutionary relationship between MIF and the GSTs has been disputed [44], the occurrence of a closely related gene (DDCT) within the Theta-class gene cluster is, if nothing else, an interesting coincidence.…”
Section: Discussionmentioning
confidence: 97%
“…Several X-ray structures for GST enzymes of the a, p and ~t classes have become available over the last five years (for reviews, see Dirr et al, 1994 andParker, 1994), followed by structures of GST enzymes from squid (Ji et al,l995), Schistosoma japonicum (Lim et al, 1994;McTigue et al, 1995), by the first X-ray structure of a 8-class GST from the fly Lucilia cuprina , and, most recently, by that of a herbicide-conjugating plant GST from Arubidopsis thaliana (Reinemer et al, 1996), which from its protein sequence falls in the proposed 4 class of GST enzymes (Blocki et al, 1993). As a consequence, the amassed data on substrate specificity and catalytic activity of glutathione S-transferases and mutants thereof, obtained by protein engineering, can now often be discussed in great structural detail.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two 0-class GST sequences from human and fish have no N-terminal tyrosine residue whatsoever. A search for conserved residues in &class GSTs suggested a well-conserved serine residue at the N-terminal as a potential H-bonding residue in theses enzymes (Blocki et al, 1993). We investigated by protein engineering methods the importance of residues Tyr6, His8 and Serl2 in DMll dichloromethane dehalogenase (Fig.…”
Section: Selection Of Amino Acids For Site-directed Mutagenesismentioning
confidence: 99%